Analysis of Factors Causing Students Learning Difficulties in Learning Science - Amaliyah, Syarifatul; Fajar, Dinar Maftukh; Aminulloh (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
This study employed a mixed method to analyze learning difficulties faced by students in seventh-grade science subjects and identify factors that cause them. This study was conducted on 96 students in the first semester. Data collection techniques were carried out using questionnaires, interviews, and documentation. The result of this study indicated that the form of a ranking of the science material in seventh grade in the first semester from the most difficult to the easiest; Heat and Its Transfers, Temperature and Its Changes, Matter Classification and Its Changes, Classification of Living Things, Energy in Living Systems, and Scientific Objects and their Observations. While the factors that cause it are internal and external factors. Internal factors include psychological aspects such as talent, interest, and emotions; and physiological aspects like minor health problems. External factors cover the family conditions; the school environment, such as learning media and infrastructure; and the community, such as the use of social media.